Aspects of complexity : minicourses in algorithmics, complexity and computational algebra : mathematics workshop, Kaikoura, January 7-15, 2000 - Downey, R. G. (Rod G.); Hirschfeldt, Denis Roman (De Gruyter series in logic and its applications., 2001)
The book contains 8 detailed expositions of the lectures given at the Kaikoura 2000 Workshop on Computability, Complexity, and Computational Algebra. Topics covered include basic models and questions of complexity theory, the Blum-Shub-Smale model of computation, probability theory applied to algorithmics (randomized alogrithms), parametric complexity, Kolmogorov complexity of finite strings, computational group theory, counting problems, and canonical models of ZFC providing a solution to continuum hypothesis. The text addresses students in computer science or mathematics, and professionals i.